FE modeling of Non-circular LRS FRP-confined concrete columns. (15th April 2022) - Mohammadi, Mohsen; Bai, Yu-Lei; Yang, Hong-Long; Lin, Guan; Dai, Jian-Guo; Zhang, Yu-Feng
Highlights: Calibrating the concrete damage plasticity model by both the active confinement pressure approach and the confinement stiffness approach. Deducing the concrete plastic flow from LRS FRP-confined concrete columns as a function of confinement stiffness. Incorporating geometrical effects in the determination of the plastic dilation angle. Abstract: In concrete columns confined with large rupture strain (LRS) fiber-reinforced polymers (FRPs), the LRS FRPs enhance the strength and ductility of concrete columns with the same mechanism as conventional FRPs by rendering passive lateral confinement pressure. However, LRS FRPs exhibit a strain capacity much larger than that of conventional FRPs. Notably, LRS FRPs have a bilinear material stiffness instead of the linear stiffness in conventional FRPs. Therefore, under axial compression, concrete confined by LRS FRPs will bear a different load path compared to that confined by conventional FRPs. This difference must be considered for finite element analysis (FEA) of LRS FRP-confined columns especially when the confinement pressure is non-uniform. To this aim, 23 samples of non-circular LRS FRP-confined concrete columns under axial monotonic compression were tested and analyzed. The variable test parameters are the aspect ratio (i.e., the depth (longer side) and width (shorter side) of the cross-sections）, the number of LRS FRP layers, and the type of LRS FRPs. For FEA, the concrete damage plasticity module (CDPM) was calibrated by both the active confinement pressure approach and the confinement stiffness approach. The active confinement pressure approach shows that the concrete plastic flow of LRS FRP-confined concrete is dominated by the secondary stiffness of the LRS FRP jacket. For the confinement stiffness approach, the concrete plastic flow is deduced from the compressive cyclic tests of cylindrical columns confined by LRS FRP jackets as a function of confinement stiffness. Results showed that the plastic dilation angle of concrete confined by LRS FRPs changes almost three times faster than that for concrete confined by conventional FRPs. The geometrical effects are included in the obtained plastic dilation angle so that a new plastic dilation angle model becomes feasible for the FEA of non-circular LRS FRP-confined concrete columns. Utilizing this new plastic dilation angle model enables the proposed plastic damage model to capture the stress strain behavior of the non-circular columns. Moreover, the non-uniformity of plastic flow on sections is captured reasonably.